2022
DOI: 10.1021/acs.joc.2c00881
|View full text |Cite
|
Sign up to set email alerts
|

BF3-Mediated Acetylation of Pyrazolo[1,5-a]pyrimidines and Other π-Excedent (N-Hetero)arenes

Abstract: An operably simple microwave-assisted BF3-mediated acetylation reaction of pyrazolo­[1,5-a]­pyrimidines and a plausible mechanism based on density functional theory (DFT) theoretical calculations for this transformation are reported. Remarkably, and to the best of our knowledge, this is the first example of the direct acetylation for the functional pyrazolo­[1,5-a]­pyrimidine (PP) core. The synthesis of this essential building block is reported in high yields using mild reaction conditions, inexpensive reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…Consequently, our previous results on constructing the dioxaborinine ring are a reliable starting point for accessing various derivatives of this heterocyclic core. 20 Additionally, it was possible to establish that the optimum temperature to treat the acetylating mixture (an excess of Ac 2 O/BF 3 ·OEt 2 ) is 60 °C. Finally, we could verify our hypothesis that the formation of the DB ring in a one-pot manner is enhanced when long reaction times are used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, our previous results on constructing the dioxaborinine ring are a reliable starting point for accessing various derivatives of this heterocyclic core. 20 Additionally, it was possible to establish that the optimum temperature to treat the acetylating mixture (an excess of Ac 2 O/BF 3 ·OEt 2 ) is 60 °C. Finally, we could verify our hypothesis that the formation of the DB ring in a one-pot manner is enhanced when long reaction times are used.…”
Section: Resultsmentioning
confidence: 99%
“…During the optimizing reaction conditions process, we observed that the uorescent by-product 6, bearing the pyrazolo[1,5-a]pyrimidine-dioxaborinine hybrid system resulting from the formation of four new bonds in a one-pot manner, is favored in long reaction times. 20 Within the most conventional photophysical applications of organic uorophores, ion recognition has been the subject of extensive study in the last two decades; 21,22 in particular, cyanide (CN − ) is one of the most concerning environmental ions. Cyanide toxicity is known because it can inhibit the mitochondrial cytochrome C oxidase and suppress oxygen transport.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations